Business Planning : 3S the art of embroidering / Muhammad Firdaus Muhammad Nawi ...[et al.] - Muhammad Nawi, Muhammad Firdaus; Mohd Fadly, Fareez; Abdullah, Nor Haliza; Mahayad Din, Siti Munirah; Mahmud, Nik Muhammad Syafiq (2008)
Our company has made a discussion to enter supply and selling our embroidery products to customer. This is because embroidery business is one of the most successful and their potential growth is big. Administration is one of the important part of our business management work effectively and professional rules. It is also can guarantee that our business to face any outcome which of course can effect our profit. In addition, it also can help the transaction in our structure of organization more arrangeable and run smoothly so the customer and banker will trust us. Then, they will be easily make a transaction with our company. 3S will be operated at No.10,Bangunan Mara 18500 Machang, Kelantan Darul Naim. From our research, this is very strategic and this place is the suitable location for our business to market our product. Due a lot of facilities that have been provided near our company such as restaurant, mini market and others. Besides, the target market is very big. Electricity has been provided by Tenaga Nasional Berhad and water from Air Kelantan SDN. BHD. Meanwhile, Telekom Malaysia will produce telephone line and internet for our business. Organization plan is the basic framework within the manager and her subordinates operate